Evolution of the degree of efficiency of the cryptocurrency market from 2014 to 2020: an analysis based on its fractal components - Abreu, Daniel Pereira Alves de; Coaguila, Robert Aldo Iquiapaza; Camargos, Marcos Antônio de (Revista de Administração da UFSM, 2022)
Objective: This study aims to analyze the evolution of the cryptocurrency market efficiency based on fractal aspects of the historical price series of 15 cryptocurrencies and a benchmark developed for this market (CRIX). Methodology: The proposed analyses start from the efficiency index proposed by Kristoufek and Vosvrda (2013), which captures long-and short-term memory biases as well as first-order autocorrelation. The database covers the period from 08/02/2014 to 12/31/2020. Using structural breakout analysis for time series, it was possible to divide the sample into five periods of analysis, and the efficiency index was calculated for each one. Findings: It was identified the existence of oscillations between the efficiency indexes over the analyzed periods, verifying a greater inefficiency at times of market upswing. In addition, it can be seen that in general this market has been gaining efficiency over the years, although it has not yet reached the absence of inefficiency. This conclusion corroborates studies on the adaptation of market efficiency based on its investors and agents. Finally, one can characterize the current scenario as a speculative bubble, which, due to the presence of the herd effect, enables the existence of arbitrage. Originality: The research in this area is still recent, as it is a new financial segment, so there are several doubts and gaps in the literature. In this sense, the adoption of a longitudinal approach to identify the evolution of efficiency of this market is not only interesting but it is also an approach little explored by the literature.